The estrogen receptor α colocalizes with proopiomelanocortin in hypothalamic neurons and binds to a conserved motif present in the neuron-specific enhancer nPE2 - de Souza, Flávio S. J. (2011)
The gene encoding the prohormone proopiomelanocortin (POMC) is mainly expressed in two regions in vertebrates, namely corticotrophs and melanotrophs in the pituitary and a small population of neurons in the arcuate nucleus of the hypothalamus. In this latter region, POMC-derived peptides participate in the control of energy balance and sensitivity to pain. Neuronal expression of POMC is conferred by two enhancers, nPE1 and nPE2, which are conserved in most mammals, but no transcription factors are yet known to bind to these enhancers. In this work, by means of a one-hybrid screening, we identify that nPE2 possesses an element recognized by transcription factors of the nuclear receptor superfamily. This element, named NRBE, is conserved in all known nPE2 enhancers and is necessary to confer full enhancer strength to nPE2-driven reporter gene expression in transgenic mice assays, indicating that the phylogenetic conservation of the element is indicative of its functional importance. In a search for candidate nuclear receptors that might control POMC we observed that estrogen receptor alpha (ESR1) - a known regulator of energy balance at the hypothalamic level - can bind to the NRBE element in vitro. In addition we observed by immunofluorescence that ESR1 is coexpressed with POMC in around 25–30% of hypothalamic neurons of males and females during late embryonic stages and adulthood. Thus, our results indicate that hypothalamic expression of POMC is controlled by nuclear receptors and establish ESR1 as a candidate regulator of POMC.